Strategi Pemerintah Kabupaten Sukabumi dalam Penguatan Peran Pusat Kegiatan Belajar Masyarakat (PKBM) Untuk Meningkatkan Capaian Pendidikan Masyarakat - Yulianti, Siska Dwi; Rosmiati, Neni; Septiana , Tina (Indra Institute Research & Publication, 2025)
Education is a fundamental right of every citizen, yet not all segments of society have equal access to formal education. This is where the Community Learning Center (PKBM - Pusat Kegiatan Belajar Masyarakat) emerges as a grassroots solution, bridging the educational gap in Sukabumi Regency. PKBM was born from the spirit of community cooperation, by the community, and for the community. This institution not only focuses on literacy eradication but also serves as a platform for skill development and equivalency programs that adapt to local needs. The uniqueness of PKBM lies in its flexibility in reaching those who are 'marginalized' from the conventional education system. To understand the dynamics and effectiveness of PKBM in Sukabumi Regency, an in-depth study was conducted using a qualitative approach. The research methodology combines various data collection techniques, including direct field observations, in-depth interviews with stakeholders, and comprehensive documentation of learning activities. The Sukabumi Regency Government recognizes PKBM's potential as a catalyst for social change. Through a comprehensive approach oriented towards community empowerment, the local government strives to optimize PKBM's role as a strategic partner in educational development. This initiative reflects the local government's commitment to building an inclusive and sustainable educational foundation, with the hope of creating positive transformation in the educational landscape of the Sukabumi region